Lupin allergy: Uncovering structural features and epitopes of ß-conglutin proteins in Lupinus Angustifolius L. with a focus on cross-allergenic reactivity to peanut and other legumes - Jimenez-Lopez, J.; Lima-Cabello, E.; Melser, S.; Foley, R.; Singh, Karambir; Alché Juan, D. (2015)
The use of sweet lupins as a new food is resulting in an increasing number of cases of allergy reactions, particularly in atopic patients with other pre-existing legume allergies. We performed an extensive in silico analysis of seed ß-conglutins, a new family of major allergen proteins in lupin, and a comparison to other relevant food allergens such as Ara h 1. We analyzed surface residues involved in conformational epitopes, lineal B- and T-cell epitopes variability, and changes in 2-D structural elements and 3D motives, with the aim to investigate IgE-mediated cross-reactivity among lupin, peanut, and other different legumes. Our results revealed that considerable structural differences exist, particularly affecting 2-D elements (loops and coils), and numerous micro-heterogeneities are present in fundamental residues directly involved in epitopes variability. Variability of residues involved in IgE-binding epitopes might be a major contributor to the observed differences in cross-reactivity among legumes.